Lithostratigraphic study of Mizozoic formations N- Palmyra petroleum potential. (Latakia University Journal -Basic Sciences Series, 2019)
The Palmyra's chain, is one of the Syrian strategic petroleum regions. Thus the petroleum companies were interested by this structure through the petro-service contracts.This study focused on petroleum potential of the Mizozoic formations in the N-Palmyra. The formation thickness variations have permitted to estimate this potentiality relating to: Kurachina dolomite, Butma, Al- Haramon, and Rutba formations. In the other side, the other formations are poor. Also, through the results of executed studies,  using the time- map data and the seismic profiles analysis, a new promising structure, El Khashabia, is proposed. In this structure a new well is suggested, which must be promising as petroleum potential.